INNOVATIONS IN THE MANAGEMENT OF CHILDREN'S NEUROINFECTIONS - N. V. Skripchenko; Yu. V. Lobzin; V. B. Voytenkov; V. E. Karev; L. A. Alekseeva; Yu. P. Vasil'yeva; A. A. Vil'nits; A. V. Klimkin (LLC "Diagnostics and Vaccines", 2017)
The article describes some topical problems of neuroinfections in children and the ways of their solutions on the basis of the experience of a leading institution - Pediatric Research and Clinical Center for Infectious Diseases. There are introduced some innovation approaches of diagnostics and therapy of bacterial purulent meningitis tested at the institution. There are described diagnostic markers of meningitis in children, method of ultrasound evaluation monitoring of the condition of kidneys, renal blood flow, adrenal glands in the patients with a fulminant course of generalized form of meningococcal infection, and innovation therapeutic approach by recombinant interleukin-2 - roncoleukin introduction to the complex therapy. There is reflected an innovation method of differential diagnostics by the determination of acute-phase protein haptoglobin in cerebrospinal fluid. There are presented the tested methods to diagnose sensorineural deafness in children with bacterial purulent meningitis, critical condition polyneuropathy, and inflammatory polyneuropathy by the technique of rehabilitation potential evaluation.